Morphometric diversity of some Nigerian accessions of Bambara groundnut (Vigna subterranea) - Osundare, O.T.; Akinyele, O.B.; Odiyi, A.C.; Abberton, M.T.; Oyatomi, O.; Paliwal, R. (Cambridge University Press, 2023)
This study evaluated the morphological diversity of some Nigerian accessions of Bambara groundnut. Field experiments were conducted in Nigeria in two locations and the phenotypic variation of Bambara groundnut accessions evaluated in 3 years (2017–2020) using a randomized complete block design. Twenty-eight quantitative and 10 qualitative traits were observed. Twenty-three out of the 28 quantitative morphological traits showed significant differences. TVSu-589 (28.85) and TVSu-670 (28.57) had the highest plant height; TVSu-572 (121.52), TVSu-271 (113.10) and TVSu-336 (104.15) had the highest 100-seed weight. Genetic variations were also observed in seed colour, terminal leaflet shape, petiole colour and eye pattern. Principal component analysis showed PC1 constituting 23.36% and PC2 constituting 15.76% of the total variation, while the first eight principal components with eigenvalues ≥1 revealed 77.28% of the total variation. Cluster analysis grouped the accessions into four groups. Based on yield data in this study, accessions TVSu-594, TVSu-350, TVSu-336, TVSu-1242, TVSu-129, TVSu-14, TVSu-179, TVSu-2100, TVSu-261 and TVSu-589 were the best for yield and are recommended for further evaluation to improve yield. This study showed that a wide range of diversity exists in Bambara groundnut of Nigerian origin that could be useful for further utilization of genetic resources and improvement.